Pengaruh Kinerja Pegawai Terhadap Kualitas Pelayanan Publik Di Kantor Bpjs Kesehatan Cabang Makassar - Robbi, Robbi; Parawu, Hafiz Elfiansya; Tahir, Nurbiah (Kajian Ilmiah Mahasiswa Administrasi Publik (KIMAP), 2021)
The purpose of this study was to determine the influence of employee performance variables on the variable quality of public services at the Makassar branch of the BPJS Healthy office. The method in this study used quantitative research methods with descriptive research type. The sample in this study amounted to 100 people and the sampling method used purposive sampling and accidental sampling techniques. The data were analyzed using simple linear regression analysis in a simultaneous and racial way. The results of this study indicated that the analysis of employee performance variables and the quality of public services was in the "good" category. Based on the results of the simple linear regression test, it showed that the employee performance variable had an effect of 60.6% on the quality of public services at the Makassar branch of the BPJS healthy office. It  concluded that the higher the employee's performance, the higher the service quality, conversely, the lower the employee's performance, the lower the quality of public service.Keywords: influence, employee performance, quality of public services